Alternative food and learning as a promising strategy for biological control - BERNADO, Ana Maria Guimarães (2015)
Several species of omnivorous predators are used in the biological control. Omnivorous predatory bugs are important natural enemies of pest that affect crops in greenhouse. It has been suggested that the use of alternative foods promote the establishment of predators on crops. Moreover, some research propose that predators can learn to associate chemical compounds with presence of food, so reducing the time of searching of natural enemies and number of pest on crops. Our aim was to find cheaper alternative foods and investigate learning ability of the predator Orius insidiosus. We evaluated the performance of O. insidiosus on four alternative foods: Ricinus sp. pollen, bee pollen, the acarid prey Tyrophagus putrescentiae and eggs of Anagasta kuehniella. Furthermore, we used synthetic methyl salicylate (MeSa) and mint oil as odour sources to study the learning ability of this predator. The predatory bugs demonstrated a better performance when fed A. kuehniella or T. putrescentiae. Our results showed that when the predator had to associate odour sources with presence of food, they showed no preference to mint oil, but showed a preference to MeSa. In addition, when the predator had to associate odour sources without food, they showed a preference to mint oil, but did not show a preference to MeSa. These results reveal that alternative and cheaper foods (e.g. T. putrescentiae) can be used with aim to sustain the predator population on rearings and possibly in crops. In addition, our results showed that O. insidiosus is able to learn, but this learning ability of predators varies with volatile compounds.